Direct Oxidative C–H Arylation of Benzoxazoles with Arylsulfonyl Hydrazides Promoted by Palladium Complexes - Yuen, On Ying; So, Chau Ming; Wong, Wing Tak; Kwong, Fuk Yee (Synlett, 2012)
This study describes a direct oxidative C-2 arylation of benzoxazoles using arylsulfonyl hydrazides as the aryl sources. A simple catalyst system [Pd(OAc)2 and Ph3P] allows the reactions to proceed smoothly under oxidative reaction conditions. Other heteroarenes such as caffeine and benzothiazole are also applicable substrates. Notably, this catalytic system tolerates halogen substituents which provides a useful complement to the current cross-coupling reactions which use aryl halides.
Keywords: palladium; arylation; arylsulfonyl chlorides; phosphine; benzoxazoles